Efficacy of Salivary and Diastase Extracts of Piper betle in Modulating the Cellular Stress in Placental Trophoblast during Preeclampsia - Padmini Ekambaram; Chithra Balan (Pharmacognosy Research, 2019)
Background: Betle leaf (BL) is an ancient herb with a potential nontoxic natural antioxidant efficacy. Oral intake and chewing betel leaves have an effort on the moving parts of salivary gland and induce salivation and detoxification; hence plays a vital role in oral hygiene. BL produces and activates various salivary enzymes which include α‑amylase, lipase, lysozyme, and lactoperoxidase. BL possess antibacterial, antioxidant, anti‑diabetic, immunomodulatory, and antihypertensive properties. Hence, it can be effective in the treatment of hypertensive disorder of pregnancy like preeclampsia (PE). Objective: In this context, two extracts of BL (Salivary BL extract [SBLE] and diastase BL extract [DBLE]), proved to impart efficient radical scavenging activity in our previous research work were utilized to analyze their efficacy on the level of 4‑hydroxy nonenal (4‑HNE), heme oxygenase‑1 (HO‑1), asymmetric dimethylarginine (ADMA), adiponectin/leptin in the trophoblast isolated from placental tissue of both normotensive and preeclamptic patients. Materials and Methods: Trophoblasts were isolated from both subjects and incubated with different extracts of Piper betle (saliva and diastase) to assess the cellular stress in placental trophoblast during PE. Results: Results demonstrate that extracts of BL exhibit a significant role in regulating 4‑HNE, ADMA, leptin, HO‑1, and adiponectin in preeclamptic trophoblasts. Still, SBLE showed relatively higher efficiency in defining the level of 4‑HNE, ADMA, leptin, HO‑1, and adiponectin in preeclamptic trophoblasts than DBLE, suggesting that it may be attributed to the interaction of the phytochemicals present in BL with the components of saliva. Conclusion: Hence, BL may be recommended as the effective natural remedy in the management of pathological complications of PE; which may preclude low birthweight babies and ensure live fetal delivery.
Keywords: Adiponectin; Diastase; Leptin; Saliva; Trophoblast.